The Influence of Principal’s Leadership and Quality of Educational Services on Students Parents’ Satisfaction - Anggraini, Titin; Putra, Alhadi Yan; Fahmi, Muhammad (Yayasan Sembilan Pemuda Indonesia, 2024)
This study aims to determine the influence of the principal’s leadership and the quality of educational services on the satisfaction of parents and students at TK IT Abatatsa Lahat Selatan. This type of research is quantitative research with a research design using an ex post facto research design. The sample in this study was 99 parents of TK IT Abatatsa Lahat Selatan students. Data collection techniques using questionnaires. Data analysis techniques use quantitative descriptive analysis techniques and multiple regression. The results of this research state that 1) there is an influence that the principal’s leadership has on the satisfaction of parents of TK IT Abatatsa Lahat Selatan students; 2) there is a significant influence on the quality of educational services on the satisfaction of parents of TK IT Abatatsa Lahat Selatan students; 3) there is a significant joint influence of the principal’s leadership and the quality of educational services on the satisfaction of parents of TK IT Abatatsa Lahat Selatan students.